2010
DOI: 10.4314/ijest.v2i5.60170
|View full text |Cite
|
Sign up to set email alerts
|

Application of Taguchi approach on investigation of formability for perforated Al 8011 sheets

Abstract: Sheet metal forming is a vital manufacturing process used in the automobile, aerospace, agriculture and architecture industries. The sheet metal is formed to various shapes to make useful components. The perforated sheets replace the solid sheet in some applications because of aesthetic appearance and low weight compared to solid sheet metal. The ability of the sheet metals to be formed into various shapes without failure is termed as formability. The formability of perforated sheet depends on chemistry of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…The age hardening behaviour of thin walled tubes for various aging temperature, time and solutionizing temperature was successfully studied and predicted by using response surface methodology. Elangovan et al (2010) studied the influence of the diameters of perforations and ligament widths on the forming limit strains. It was observed that the forming limit strains were increased with the ligament width and decreased with diameter of perforations.…”
Section: Introductionmentioning
confidence: 99%
“…The age hardening behaviour of thin walled tubes for various aging temperature, time and solutionizing temperature was successfully studied and predicted by using response surface methodology. Elangovan et al (2010) studied the influence of the diameters of perforations and ligament widths on the forming limit strains. It was observed that the forming limit strains were increased with the ligament width and decreased with diameter of perforations.…”
Section: Introductionmentioning
confidence: 99%
“…In the Taguchi method, orthogonal arrays and analysis of variance (ANOVA) are used as tools of analysis. This method can minimize the number of experiments using a statistical design of experiments …”
Section: Resultsmentioning
confidence: 99%
“…These results can be analysed and compared to bring out the common outcomes. An analytical method is presented for predicting the forming limit diagrams, which were achieved during the sheet metal forming operations, for the sheets having isotropy nature [2]. Results from this analysis are compared with the experimental data for AA3105 and AA8011 aluminium alloys.…”
Section: Introductionmentioning
confidence: 98%
“…Extensive research on its formability aspects is required to develop useful components of complex shapes [1]. The ability of the sheet metals to be formed into various shapes without failure is termed as formability [2]. In the past decade, many researchers investigated the results of mechanical properties and forming and fracture limit strains of various aluminium alloys.…”
Section: Introductionmentioning
confidence: 99%